Advancing the Learning Agenda in Jewish Education - Levisohn, Jon A.; Kress, Jeffrey S. (Academic Studies Press, 2018)
Jewish educational projects and programs are thriving, attracting philanthropic support for exciting and creative approaches in every sector and setting. But underneath that energy, we are not as clear as we ought to be about desired outcomes, the kinds of learning needed to achieve these, and how those kinds of learning actually occur. This volume is the first of its kind to bring together scholars from inside Jewish education and from the learning sciences. It offers a set of critical perspectives on learning, sometimes borrowing models from other domains (such as science) and sometimes examining specific domains within Jewish education (such as havruta learning or the learning of Jewish history). Collectively, these contributions help to advance a smarter, sharper conversation about Jewish learning that matters.